Pengaruh Country Of Origin, Brand Image, dan Persepsi Kualitas Terhadap Niat Beli Hp Xiaomi (Studi Pada Mahasiswa STIE Tenggarong yang berada di Muara Badak) - SEPTIANI, AYU SHERINA; PUTRI, EVA NOORHYA AKHMAR RAMADHAN (I-Con Media, 2022)
The Influence of Country Of Origin, Brand Image and Quality Perceptions of Intention to Buy Xiaomi Cell Phones (Study of Tenggarong STIE Students in Muara Badak). The purpose of this study was to determine the effect simultaneously and partially of the variables of country of origin, brand image and perceived quality of purchase intention for Xiaomi cellphones (study of Tenggarong STIE students residing in Muara Badak). The analysis in this study is multiple regression, processed using SPSS, with a total of 26 respondents. The results obtained simultaneously show that the variables of country of origin, brand image and perceived quality have a significant effect on purchase intention of Xiaomi cell phones. Partially, country of origin has a significant influence on purchase intentions of Xiaomi cellphones, brand image has a significant effect on purchase intentions of Xiaomi cellphones and perceived quality has a significant effect on purchase intentions of Xiaomi cellphones.